ESTETIK ORNAMEN MASJID DI KOTA PADANG - Sundari, Sri; Yulimarni, Yulimarni (Jurnal Seni, Desain dan Budaya)
AbstractThe study was conducted aiming to find the aesthetic values that exist in the mosque building ornament in the city of Padang. The development and spirit of changing times has accompanied the development of the Mosque in Padang City, not only in the function and role of the Mosque, but also seen from the model of the mosque building and ornaments attached to the building. To achieve this goal the approach used in this paper is the aesthetic approach, and multi-disciplinary approach. The aesthetic value of mosque building ornaments can be viewed through the quality structures that make up beauty; first, unity; that each element in the mosque's ornament is a unified and mutually supportive unit, summarized in the quality of art consisting of rhythm, lines and shapes. Second, harmony (harmony); placement of motifs on the mosque building shows harmony by considering the balance between the shape of the motif with the field of placement. Third; symmetry; Almost all the ornaments contained in the mosque building contain symmetrical elements in vertical and horizontal forms. Symmetry can be seen in the motif lines and also the building lines themselves. Fourth; balance (balance); Mosque ornaments in the city of Padang, has three types of balance, namely; symmetrical balance, asymmetrical balance, and centering balance. And the fifth resistance (contras); the contrast does not only occur because of differences in the size of the motif, the contrast can also be seen from the shape and color of the ornament attached to the mosque building.Keywords : Aesthetic, Ornaments, MosqueAbstrakPenelitian dilakukan bertujuan untuk menemukan nilai-nilai estetik yang ada pada ornament bangunan Masjid di Kota Padang. Perkembangan dan semangat zaman yang berubah telah mengiringi perkembangan Masjid di Kota Padang, tidak hanya dalam fungsi dan peran Masjid, tetapi juga terlihat dari model bangunan Masjid dan ornamen yang melekat pada bangunannya.Untuk mencapai tujuan tersebut pendekatan yang digunakan dalam tulisan ini adalah pendekatan estetika, dan pendekatan multi disiplin. Nilai estetik ornamen bangunan Masjid dapat ditinjau melalui struktur kualitas pembentuk keindahan; pertama, kesatuan (unity); bahwa setiap unsur dalam ornamen Masjid merupakan satu kesatuan yang utuh dan saling mendukung, yang terangkum dalam kualitas seni yang terdiri dari irama, garis dan bentuk. Kedua, keselarasan (harmony); penempatan motif pada bangunan Masjid menunjukan keselarasan dengan mempertimbangkan keseimbangan antara bentuk motif dengan bidang penempatannya. Ketiga; kesetangkupan (symetry); Hampir semua ornamen yang terdapat pada bangunan Masjid mengandung unsur simetris dalam bentuk vertikal maupun horizontal. Simetri dapat terlihat pada garis motif dan juga garis bangunan itu sendiri. Keempat; keseimbangan (balance); ornamen bangunan Masjid di kota Padang, memiliki tiga jenis keseimbangan yaitu; keseimbangan simetris, keseimbangan asimetris, dan keseimbangan memusat. Dan kelima perlawanan (contras); kontras tidak hanya terjadi karena perbedaan ukuran motif saja, kontras juga terlihat dari bentuk dan warna ornament yang melekat pada bangunan Masjid.Kata kunci : Estetik, Ornamen, Masjid